P PENURUNAN MINYAK DAN LEMAK PADA LIMBAH CAIR KANTIN MENGGUNAKAN MODIFIKASI GREASE TRAP MEDIA ZEOLIT (Politeknik Kesehatan Kemenkes Bandung, 2022)
Canteen liquid waste at PT.X contains oil and fat that comes from the process of washing food ingredients, washing cooking utensils, and washing eating utensils have been used. Oils and fats are as dangerous for aquatic life and humans if their value exceeds the quality standard. The purpose of this thesis was to determine the effect of variations in contact time of zeolite media using a modified grease trap on the oil and fat content of the canteen liquid waste of PT.X. This is experimental research with a research design is a pre-test post-test without control, and the sampling technique used is composite sampling. The population is all of the canteen liquid waste of PT.X. Sample was some of the canteen liquid waste at PT.X given treatment. Analysis showed that the average reduction in oil and fat content in the treatment was 22,92 mg/L; 26,95 mg/L, and 27,45 mg/L. The statistical test used is a One-Way ANOVA test. Based on the result of the examination, it is known that the percentage of reduction in oil and fat levels is the contact time of zeolite 55 minutes (75,14 %), 60 minutes (99,78%), and 70 minutes (99,88%). The conclusion of this research is that there is an effect of differences in the contact time of zeolite media on oil and fat content using a modified grease trap in liquid waste produced by PT.X. Industry can apply canteen liquid waste treatment using grease traps modified and carry out regular maintenance of equipment.